DEVELOPMENT OF A CHILD WITH CONGENITAL LEUKEMIA AND MATERNAL RESILIENCY (Fiep Bulletin - online, 2014)
In the just born, the leukemia is extremely rare, representing about 1% of all the cases of infantile leukemia.  Under the glance of the ecological perspective, a child's mother's resiliency with congenital leukemia can soften or to exacerbate the suffering lived by both during the process of disease and treatment of the cancer.  Thus, that report describes a child's case with leukemia congenital, with emphasis in the child's development and in the profile of the mother's resiliency. The child presented a low percentile of the expected for your age, with low weight and stature, but in the cephalic perimeter the measure (44 cm) what is normal for your age. In the evaluation of the child's behavior, the same presented difficulty in accomplishing two tasks in the evaluation of the strip of the nine months, equivalent your chronological age, being classified with "possible delay in the development". The mother presented a lower resiliency profile. We believed that the possible delay in the child's development is due to the process of disease and treatment of the leukemia, demonstrating the relevance of the detection of problems in the development and turning fundamental the precocious intervention, with the intention of stimulating the child's potential maximum. The mother's resiliency should be stimulated to optimize the treatment and the child's recovery.
Keywords: resiliency; child development; leukemia